Processing method of corneal contact lens material and manufacturing method of corneal contact lens
By controlling the relationship between the temperature of the heat treatment device and the glass transition temperature of the resin material, and combining multi-container hot pressing and molding processes, the problem of unstable strength and toughness of the resin material after hot pressing was solved, thus achieving efficient production and excellent performance of corneal contact lens materials.
Patent Information
- Application Number
- CN202210254969.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-03-15
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2042-03-15
AI Technical Summary
In existing technologies, the strength and toughness of resin materials vary during hot pressing, making it difficult to maintain stability under different environments and affecting the quality of corneal contact lenses.
By controlling the relationship between the temperature of the heat treatment device and the glass transition temperature of the resin material, the resin material is kept in an elastic state during the hot pressing process. Multiple containers are used for hot pressing, combined with molding process, to control the shape and concave arc surface of the blank after hot pressing. A detachable stripper block is used to adjust the concave arc surface requirements and optimize the processing conditions.
It improves the strength and toughness of corneal contact lens materials, simplifies subsequent processing steps, increases production efficiency, and reduces manufacturing costs.
Smart Images

Figure CN116787668B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of corneal contact lens manufacturing, and specifically to a method for processing corneal contact lens materials having good bending strength by using a hot pressing process to manufacture corneal contact lenses, in particular, to manufacture corneal contact lens materials for hard gas permeable contact lenses. Background Art
[0002] There are two important indicators for contact lenses, one is the DK value (oxygen permeability coefficient), and the other is the bending strength. In order to meet people's needs for wearing contact lenses for a long time, the use of materials with high DK values to improve comfort has become the mainstream choice. Generally speaking, as the DK value increases, the durability against instantaneous impact and bending such as lens breakage will inevitably decrease.
[0003] In order to take into account both the comfort and safety of corneal contact lenses, Japanese patent No. JP4087947 discloses a method for manufacturing a gas-permeable hard corneal contact lens. According to the manufacturing method, the resin material is subjected to a heat pressing treatment, specifically, the resin material is heated to its glass transition temperature, and then stretched laterally by applying vertical pressure to replace the random molecular chains of the material polymer with a directional molecular chain structure. In addition, because the resin material does not melt after being heated to the glass transition temperature, the volume of the resin material does not change due to being stretched. Through the above heat pressing process, it is possible to achieve consistent orientation of the molecular complex in the stretching direction without changing the material composition or polymerization conditions, so that the hard corneal contact lens has a higher bending strength, and the material's DK value or refractive index and other properties, as well as the manufacturing method, will not change.
[0004] Although the resin material has higher strength and toughness after heat pressing, it is difficult to measure whether the resin material in the mold is accurately heated to the glass transition temperature because the heat pressing of the resin material is carried out in a mold. Therefore, the performance of the resin material in strength and toughness after heat pressing may be significantly different when heat pressed in different environments. Therefore, when manufacturing corneal contact lenses, how to implement the heat pressing process so that the resin material after heat pressing has better strength and toughness is a problem in the prior art. Summary of the invention
[0005] In view of the above problems, the present invention provides a method for processing corneal contact lens materials which can ensure that the strength and toughness of the resin material after heat pressing treatment reach stable expected values.
[0006] In order to achieve the above object, the present invention provides a method for processing corneal contact lens material, comprising the following steps:
[0007] A pre-processing step of providing a blank of a specified size made of a resin material;
[0008] A hot pressing preparation step, placing the blank in a pressing assembly, and placing the pressing assembly and the blank as a whole in a heat treatment device with an internal temperature of a specified temperature;
[0009] The hot pressing step heats the pressing assembly and the blank as a whole for a specified time, and then presses the blank to form a corneal contact lens material.
[0010] The relationship between the predetermined temperature T of the heat treatment device and the glass transition temperature Tg of the blank satisfies the conditions of T-Tg>0°C and T-Tg<50°C.
[0011] According to the processing method of the corneal contact lens material provided by the present invention, since the pressing assembly and the blank are placed as a whole in a heat treatment device with an internal temperature of a specified temperature, and as the heating time increases, the temperature of the blank in the pressing assembly will inevitably increase gradually and approach the specified temperature T of the heat treatment device. Therefore, in order to ensure that the temperature of the blank in the pressing assembly is close to or above the glass transition temperature, and the resin material constituting the blank is kept in an elastic state, and the softness can make the blank deform under the action of external force, it is necessary to make the specified temperature T of the heat treatment device meet T-Tg>0℃.
[0012] In addition, the inventors of the present invention have found through experiments that when the specified temperature T of the heat treatment device is set at not higher than the glass transition temperature of the blank by 50°C, after heating for a specified time, the strength of the manufactured corneal contact lens material is excellent. In addition, when the specified temperature T of the heat treatment device is set too high, it is easy to cause the resin material of the blank to decompose, thereby reducing the strength of the manufactured corneal contact lens material and causing adhesion to the pressing component. Therefore, the specified temperature T of the heat treatment device preferably satisfies T-Tg<50°C.
[0013] In a preferred technical solution of the present invention, the relationship between the specified temperature T in the hot pressing step and the glass transition temperature Tg of the blank satisfies the conditions of T-Tg>0°C and T-Tg<30°C. More preferably, the relationship between the specified temperature T in the hot pressing step and the glass transition temperature Tg of the blank satisfies the conditions of T-Tg>10°C and T-Tg<30°C.
[0014] According to this preferred technical solution, it has been found through experiments that when the prescribed temperature T of the heat treatment device is not higher than the glass transition temperature of the blank by 30°C, the strength of the manufactured corneal contact lens material is the best. On this basis, the lower the prescribed temperature T of the heat treatment device is, the more it can suppress the decomposition of the resin material constituting the blank due to excessive temperature and the resulting changes in physical properties. At the same time, when the prescribed temperature T of the heat treatment device is set 10°C higher than the glass transition temperature of the blank, the time of the blank heating process can be shortened and the production efficiency can be improved compared to when the prescribed temperature T of the heat treatment device is the same as or slightly higher than the glass transition temperature of the blank. Therefore, it is considered more preferred that the prescribed temperature T of the treatment device satisfies the conditions of T-Tg>10°C and T-Tg<30°C.
[0015] In a preferred embodiment of the present invention, the blank comprises a copolymer of methacrylate siloxane and methacrylate fluoroalkyl ester.
[0016] According to this preferred technical solution, the corneal contact lens material manufactured by utilizing the physical properties of methacrylate siloxane and methacrylate fluoroalkyl ester copolymer will have good air permeability and wettability.
[0017] In a preferred technical solution of the present invention, the pressing assembly includes a press seat, a press block, and a container arranged in the press seat and having a space for placing the blank. The blank is a columnar blank. During the hot pressing step, the press block is pressed downward to cause the heat-softened blank to extend radially outward to fill the space in the container.
[0018] According to the preferred technical solution, after the hot pressing preparation step, the pressing assembly and the blank are placed in a heat treatment device with an internal temperature of a specified temperature, and in the hot pressing step, the heat-softened blank is pressed to extend radially outward to fill the space of the container, so that the deformation of the blank in the longitudinal and transverse directions is restricted during the hot pressing process, making the hot pressing process more uniform. At the same time, in the preferred technical solution, the shape of the blank after hot pressing is determined by the mold, that is, the blank after hot pressing has the same shape, and the same post-processing steps can be used for the corneal contact lens material formed after hot pressing, thereby improving production efficiency.
[0019] In a preferred technical solution of the present invention, the pressing assembly includes a plurality of containers stacked along the force application direction of the pressing block, and the plurality of containers are accommodated between the pressing seat and the pressing block.
[0020] According to the preferred technical solution, since a plurality of containers are stacked along the force direction of the pressing block, each time the pressing block applies pressure, a plurality of blanks can be hot-pressed simultaneously, thereby improving production efficiency.
[0021] In a preferred technical solution of the present invention, at least a portion of the bottom surface in the container is formed as a convex arc surface.
[0022] According to the preferred technical solution, since the bottom surface inside the container is at least partially formed as a convex curved surface, the blank is subjected to a molding process at the same time as the hot pressing process. Even if the shape of the blank after the hot pressing process, that is, the corneal contact lens material has a concave curved surface that matches the shape of the convex curved surface on the bottom surface of the container, the number of subsequent cutting times can be reduced when the corneal contact lens material is subsequently cut to make a corneal contact lens, thereby improving production efficiency and reducing manufacturing costs.
[0023] In a preferred technical solution of the present invention, the container is an integrally formed mold.
[0024] According to the preferred technical solution, the containers are integrally formed, and the shape of each container, especially the shape of the convex arc surface formed on the bottom surface of the container, can be accurately controlled, thereby ensuring the stability of the concave arc surface formed by the corneal contact lens material after hot pressing.
[0025] In a preferred technical solution of the present invention, the container is composed of a bottomless cylindrical mold and a stripping block matching the bottom of the bottomless cylindrical mold. The stripping block is detachably engaged with the bottom of the bottomless cylindrical mold to form a space for placing the blank, and the blank is placed on the upper surface of the stripping block.
[0026] According to the preferred technical solution, because the bottomless cylindrical mold and the stripping block are detachable, when it is necessary to process and manufacture corneal contact lens materials with different concave arc surfaces, the arc surface only needs to be replaced with a stripping block that matches the concave arc surface of the corneal contact lens material to be manufactured, and the bottomless cylindrical mold can be universal. Because, in the process of processing corneal contact lens materials, different corneal contact lenses have different requirements for the curvature of the concave arc surface of the corneal contact lens material. Compared with adjusting or replacing the entire container, only adjusting the stripping block can cope with different requirements for the concave arc surface of the corneal contact lens material without replacing the entire container, which has low production costs and high production efficiency.
[0027] The bottomless cylindrical mold forms the peripheral wall of the container, and the detachable stripping block forms the bottom surface of the container after being matched and embedded with the bottomless cylindrical mold. Specifically, the stripping block can be embedded in the bottomless cylindrical mold by matching the groove on the inner surface of the bottomless cylindrical mold with the protrusion on the outer side of the stripping block.
[0028] In a preferred technical solution of the present invention, the specified size of the blank provided in the pretreatment step is determined according to the internal space size of the container and the hot pressing elongation of the resin material, so that the size of the blank after hot pressing matches the internal space size of the container.
[0029] According to the preferred technical solution, since the internal space size of the container (equivalent to the size of the blank after hot pressing) and the hot pressing elongation of the resin material are known, and the volume of the blank does not change before and after hot pressing, the specified size (diameter and height) of the blank to be provided in the pretreatment step can be calculated by the size (diameter and height) of the blank after hot pressing, that is, the size of the manufactured corneal contact lens material.
[0030] Among them, the hot pressing elongation refers to the rate of change of the diameter of the blank.
[0031] By adjusting the specified size of the blank provided in the pretreatment step through the method in the preferred technical solution, the blanks with different elongation rates can have the same shape after the hot pressing treatment. In this way, when the blank after the hot pressing treatment, i.e., the manufactured corneal contact lens material, is subsequently processed to form a corneal contact lens, the processing conditions will be the same, thereby reducing the complexity of the processing and improving the production efficiency.
[0032] The present invention also provides a method for manufacturing a corneal contact lens, comprising a cutting step, wherein the corneal contact lens material formed by the processing and manufacturing method in any of the above technical solutions is cut to manufacture the corneal contact lens.
[0033] The technical solution provided by the present invention has the following technical effects:
[0034] (1) One hot pressing process can process multiple blanks, improving manufacturing efficiency;
[0035] (2) Controlling the blanks to have the same shape after hot pressing can simplify the subsequent processing conditions;
[0036] (3) Temperature control of the heat treatment device can improve the strength of the contact lens material;
[0037] (4) Combining the molding process with hot pressing can reduce the number of cuts required in the cutting step.
[0038] The present invention also provides a hard gas permeable contact lens for corneal reshaping, which adopts the manufacturing method of the corneal contact lens.
[0039] Compared with general corneal contact lenses, rigid gas permeable contact lenses for orthokeratology are thinner and require higher mechanical properties (strength and toughness) of corneal contact lens materials. Rigid gas permeable contact lenses for orthokeratology manufactured by the method for manufacturing corneal contact lenses provided by the present invention not only meet the thickness requirements, but also have better performance in strength and toughness. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 is a flow chart of a method for processing a corneal contact lens material in an embodiment of the present invention;
[0041] Figure 2 Schematic diagram of the composition of the pressing assembly when the pressing block is not pressed down in the embodiment of the present invention;
[0042] Figure 3 Schematic diagram of the composition of the pressing assembly when the pressing block is pressed down in an embodiment of the present invention;
[0043] Figure 4 is a comparison diagram of the cutting steps of blanks obtained by different hot pressing methods in an embodiment of the present invention;
[0044] Figure 5 is a schematic diagram of another type of pressing assembly when the pressing block is not pressed down in an embodiment of the present invention;
[0045] Figure 6 It is a schematic diagram of another pressing assembly when the pressing block is pressed down in an embodiment of the present invention;
[0046] Figure 7 A testing device for testing the strength of a contact lens manufactured according to an embodiment of the present invention;
[0047] Figure 8 This is the experimental result in Experimental Example 1.
[0048] Description of reference numerals:
[0049] Pressing assembly 10; press seat 1; press block 2; container 3; bottomless cylindrical mold 31; stripping block 32; blank 4 (blank 4a after hot pressing); clamp 50; corneal contact lens 60. DETAILED DESCRIPTION
[0050] The preferred embodiments of the present invention are described below with reference to the accompanying drawings. It should be understood by those skilled in the art that these embodiments are only used to explain the technical principles of the present invention and are not intended to limit the scope of protection of the present invention. Those skilled in the art can make adjustments to them as needed to adapt to specific application scenarios. It should also be noted that, for ease of description, only the parts related to the invention are shown in the accompanying drawings.
[0051] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0052] In the existing method for manufacturing corneal contact lenses, there is a step of enhancing the strength of the material through a hot pressing process. The resin materials subjected to hot pressing in different environments also have obvious differences in strength and toughness after hot pressing. Therefore, when manufacturing corneal contact lenses, how to control the hot pressing process so that the resin material after hot pressing has better strength and toughness is a problem in the prior art. The present invention provides a method for processing corneal contact lens materials and a method for manufacturing corneal contact lenses.
[0053] (Resin material composition)
[0054] In the processing method of the corneal contact lens material of the present invention, a gas permeable hard lens material is used as the resin material constituting the blank. The selection of the material is not particularly limited, and those skilled in the art can appropriately select from known materials. Preferably, the blank comprises a copolymer of methacrylate siloxane and methacrylate fluoroalkyl ester, which has good gas permeability and wettability.
[0055] Examples of the silicon-containing (meth)acrylate monomer that can be used in the present invention include tris(trimethylsiloxy)silylpropyl, methacrylate siloxane, and the like.
[0056] Examples of the (meth)acrylate having a fluorine-substituted alkyl group that can be used in the present invention include trifluoroethyl methacrylate and / or trifluoroethyl acrylate, and fluoroalkyl methacrylate.
[0057] A highly air-permeable material can be obtained by combining the above-mentioned silicon-containing (meth)acrylate monomer and the (meth)acrylate having a fluorine-substituted alkyl group. The air permeability of the material can be adjusted by adjusting the composition ratio of the two. The present invention has no particular limitation on the composition ratio of the two.
[0058] On this basis, in order to make the lens material have good wettability to meet the user's demand for the comfort of corneal contact lenses, hydrophilic monomers can be appropriately added, for example, vinyl pyridine, vinyl pyrrolidone, etc.
[0059] The following is an example of the processing method of the corneal contact lens material of the present invention.
[0060] (Forming of blank)
[0061] In the pre-processing step of providing a blank of a specified size made of a resin material, if the size of the blank before hot pressing is not limited, for example, all the blanks before hot pressing have the same size and shape. In this case, the blank after hot pressing has different shapes due to the different elongation of the resin material. The subsequent cutting step needs to adjust different cutting conditions according to these different shapes, which increases the difficulty of the subsequent manufacturing process. For this reason, reference Figure 1 In the pretreatment step of the present invention, a blank of a predetermined size made of a resin material is provided. Preferably, the predetermined size of the blank to be provided in the pretreatment step is determined based on the size of the corneal contact lens material produced after hot pressing (i.e., the internal space size of the container 3) and the hot pressing elongation of the resin material.
[0062] Specifically, in some embodiments, the blank 4 before hot pressing and the blank 4a after hot pressing (i.e., the corneal contact lens material obtained by processing according to the embodiment of the present invention) are both cylindrical, and the size of the blank 4a after hot pressing is 12 mm in diameter and 3 mm in height. Then, the size of the blank 4 before hot pressing will be adjusted according to the hot pressing elongation of different resin materials, for example:
[0063] Elongation: 33%;
[0064] Elongation = (diameter of the blank after hot pressing - diameter of the blank before hot pressing) / diameter of the blank after hot pressing,
[0065] The above formula can be used to calculate that the diameter of the blank before hot pressing is 8 mm;
[0066] Since the volumes of the blank 4 before hot pressing and the blank 4a after hot pressing do not change, it can be calculated that the height of the blank 4 before hot pressing is 6.75 mm.
[0067] As in the above example, the dimensions of the blank 4 before hot pressing at different elongation rates can be obtained by this method, as shown in the following table:
[0068]
[0069]
[0070] (Specified temperature of heat treatment equipment)
[0071] In the embodiment of the present invention, in the hot pressing preparation step, the pressing assembly 10 and the blank 4 placed in the pressing assembly 10 are placed in a heat treatment device (not shown) whose internal temperature is a specified temperature T. In addition, during the processing and production process, although the blank 4 placed in the pressing assembly 10 will gradually increase in temperature and soften as the heating time increases, the heating time in the heat treatment device should not be too long, so that the temperature of the blank 4 in the pressing assembly 10 will be lower than the specified temperature T of the heat treatment device. In particular, for the use of similar Figure 2 When the middle pressing assembly 10 is hot-pressing, the actual temperature of the multiple blanks 4 inside is difficult to measure during hot pressing. At this time, it is more feasible and easier to operate to indirectly control the temperature of the blanks 4 by controlling the specified temperature T of the heat treatment device.
[0072] Therefore, in order to ensure that the temperature of the blank 4 in the pressing assembly 10 is above the glass transition temperature, so that the resin material constituting the blank 4 is kept in a softened state, and the softness can make the blank 4 deform under the action of external force, it is necessary to make the prescribed temperature T of the heat treatment device satisfy T-Tg>0, where Tg is the glass transition temperature of the blank 4. At the same time, when the prescribed temperature T of the heat treatment device is set to be 10°C higher than the glass transition temperature of the blank 4, compared with the prescribed temperature T of the heat treatment device being the same as or slightly higher than the glass transition temperature of the blank 4, the time of the heating process of the blank 4 can be shortened, and the production efficiency can be improved, so it is considered to be more preferred.
[0073] In addition, the inventors of the present invention have found through experiments that when the prescribed temperature T of the heat treatment device is set at not higher than the glass transition temperature of the blank 4 of 50°C, after heating for a prescribed time, the corneal contact lens material produced has the best performance in terms of strength. In addition, if the prescribed temperature T of the heat treatment device is too high, it is easy to cause the decomposition of the resin material constituting the blank 4 and produce adhesion with the pressing component 10. Therefore, the prescribed temperature T of the heat treatment device preferably satisfies T-Tg<50°C. On this basis, the lower the prescribed temperature T of the heat treatment device, the more it can suppress the decomposition of the resin material constituting the blank 4 and the resulting changes in physical properties. Therefore, it is considered more preferred that the prescribed temperature T of the heat treatment device satisfies the condition of T-Tg<30°C.
[0074] The glass transition temperature Tg of the blank 4 can be measured by conventional glass transition temperature measurement methods, such as thermogravimetric method, dynamic mechanics method, torsion pendulum method, and the like.
[0075] In the experiment, various resin materials with different glass transition temperatures were subjected to hot pressing treatment. After heating for a specified time, the difference between the specified temperature T of the heat treatment device and its glass transition temperature Tg was recorded each time a high-strength material was obtained. It was found that the differences almost all fell within the range of 50°C.
[0076] However, when the difference between the specified temperature T of the heat treatment device and the glass transition temperature Tg is close to 50°C, the blank 4 and the pressing assembly 10 stick to each other several times. Therefore, it is more preferable to control the difference between the specified temperature T of the heat treatment device and the glass transition temperature Tg of the blank 4 within a range of 30°C.
[0077] The following are examples:
[0078] When the blank 4 formed of a resin material having a Tg of about 110° C. is subjected to a hot press treatment at a predetermined temperature T between 120° C. and 130° C., a high-strength material can be obtained.
[0079] When the blank 4 formed of a resin material having a Tg of about 70° C. is subjected to a hot press treatment at a predetermined temperature T between 100° C. and 120° C., a high-strength material can be obtained.
[0080] From the above examples, it can be seen that different resin materials can be hot pressed under the conditions of T-Tg>0 and T-Tg<50°C, and ideal high-strength materials can be obtained under the relationship between the specified temperature T of the heat treatment device and the glass transition temperature Tg of the blank 4.
[0081] (Pressure assembly for hot pressing step)
[0082] Figure 2 This is a schematic diagram of the composition of the pressing assembly when the pressing block is not pressed down, refer to Figure 2 The pressing assembly 10 includes a press seat 1, a press block 2 and a container 3. In the hot pressing preparation step, a columnar blank 4 is placed in the container 3, and the container 3 is placed in the press seat 1. When the press block 2 is pressed down, the heat-softened blank 4 will extend radially outward to fill the inside of the container 3. In the subsequent hot pressing step, the heat-softened blank 4, after being subjected to the force of the press block 2, extends radially outward to fill the container 3, so that during the hot pressing process, the deformation of the blank 4 in the longitudinal and transverse directions is restricted, making the hot pressing process more uniform.
[0083] Figure 3 This is a schematic diagram of the composition of the pressing assembly when the pressing block is pressed down, refer to Figure 3 The shape of the blank 4a after hot pressing treatment (that is, the corneal contact lens material manufactured by the present invention) is determined by the shape of the container 3, that is, after hot pressing treatment, even the blanks 4 composed of different resin materials and with different hot pressing elongation rates will have the same shape, and can be cut and processed in the same post-processing steps to manufacture corneal contact lenses, thereby improving production efficiency.
[0084] Preferably, refer to Figure 2The pressing assembly 10 includes a plurality of vertically stacked containers 3, which are accommodated in the pressing seat 1 and stacked along the force direction of the pressing block 2. In this way, the pressing block 2 can perform hot pressing treatment on multiple blanks 4 at the same time by pressing down vertically once, thereby improving production efficiency.
[0085] Among them, Figure 2 As shown, a blank 4 of a certain height is placed between two adjacent containers 3. When the pressing block 2 is not pressed down, the two adjacent containers 3 are in a first relative position and remain stationary with respect to each other. When the pressing block 2 starts to be pressed down, the two adjacent containers 3 move relative to each other. When the hot pressing is finished, as shown in FIG. Figure 3 As shown, two adjacent containers 3 are stationary at a second relative position.
[0086] The specific structure of the container 3 can be selected according to actual needs. Figure 2 The container 3 provided in the embodiment of the present invention can achieve the following three effects: first, the blank 4 in hot pressing is restricted in the horizontal and vertical directions to make the hot pressing process uniform; second, multiple blanks 4 can be processed in one hot pressing step to improve production efficiency.
[0087] Preferably, refer to Figure 2 and Figure 3 , the bottom surface inside the container 3 is formed as a convex arc surface.
[0088] The bottom surface inside the container 3 is formed into a convex arc surface, which is equivalent to performing a molding process on the blank 4 while performing a hot pressing process, so that the blank 4a after the hot pressing process (i.e., the corneal contact lens material manufactured by the present invention) has a concave arc surface, which can reduce the number of subsequent cutting times for processing corneal contact lenses and improve production efficiency.
[0089] Specifically, refer to Figure 4 , hot pressing is performed on completely identical blanks A and B. The bottom surface of the container 3 used by blank A is a plane, and blank A after hot pressing is a cylindrical material. In the subsequent cutting step for processing corneal contact lenses, because the corneal contact lenses have high requirements for curvature, multiple cuttings (for example, N cuttings) are required to achieve the specified curved surface shape; while the bottom surface of the container 3 used by blank B is a convex arc surface, and blank B after hot pressing will have a concave arc surface. At this time, the concave arc surface of blank B has a certain curvature, and the beveling process is performed on this basis. Compared with blank A, only a fewer number of cuttings (for example, M cuttings, M < N) are required to achieve the same effect as blank A. Therefore, not only the production efficiency is improved, but also the service life of the cutting tool is extended and the manufacturing cost is reduced because the number of cuttings is reduced.
[0090] As a preferred embodiment of the present invention, refer to Figure 5 and Figure 6 , Figure 5 and Figure 6 The container 3 shown is composed of a bottomless cylindrical mold 31 and a stripping block 32 matching the bottom of the bottomless cylindrical mold 31. The stripping block 32 is detachably engaged with the bottom of the bottomless cylindrical mold 31 to form a space for placing the blank 4. In other words, the bottom surface of the container 3 is the upper surface of the stripping block 32, and the blank 4 is placed on the upper surface of the stripping block 32.
[0091] The bottomless cylindrical mold 31 constitutes the peripheral wall of the container 3, and the stripping block 32 constitutes the bottom surface of the container 3. The stripping block 32 can be embedded in the bottom of the bottomless cylindrical mold 31 by matching the groove on the inner surface of the bottomless cylindrical mold 31 with the protrusion on the outer side of the stripping block 32.
[0092] When it is necessary to manufacture corneal contact lens materials with different concave arc surfaces, since the bottomless cylindrical mold 31 and the stripping block 32 are detachable, it is only necessary to replace the stripping block 32 with a shape that matches the concave arc surface of the corneal contact lens material to be manufactured, without replacing the entire container 3, and the bottomless cylindrical mold 31 can be universal. Therefore, in the processing of corneal contact lens materials, different corneal contact lenses have different requirements for the concave curvature of the corneal contact lens material. Compared with adjusting the entire container 3, only adjusting the stripping block 32 can cope with different requirements for the concave arc surface of the corneal contact lens material, which is considered to be a more preferred approach.
[0093] (Heating method in hot pressing step)
[0094] In order to heat the entire press assembly 10 , a constant temperature box may be used as a heat treatment device (not shown) for heating the press assembly 10 .
[0095] In the hot pressing step, the pressing assembly 10 and the plurality of blanks 4 therein are placed in a constant temperature box as a whole for heating, so that the blanks 4 in the pressing assembly 10 can be heated evenly.
[0096] Particularly in the case where a plurality of blanks 4 are arranged vertically in the pressing assembly 10, it is considered preferable to use a constant temperature box as a heat treatment device for overall heating.
[0097] (Contact lens strength test method)
[0098] The corneal contact lens material formed by processing using the above-mentioned embodiment of the present invention is further processed to form a corneal contact lens, and the corneal contact lens is used as a sample to measure the compression load. Figure 7The test device shown includes a holder 50 and a contact lens 60. According to the provisions of ISO and national standards, the contact lens 60 is pressed into the holder 50 at a certain speed to measure the load when it is pushed 70% or the load value when it breaks.
[0099] [Experimental Example 1]
[0100] The glass transition temperature Tg of the blank 4 is 110°C.
[0101] Experimental method: Place the blank 4 in the pressing assembly 10, and place the pressing assembly 10 and the blank 4 as a whole in a heat treatment device with an internal temperature of a specified temperature T=130°C and an internal temperature of a specified temperature T=150°C, respectively. After heating for 15 minutes, use the pressing block 2 to press and fix for 5 minutes.
[0102] The various steps of the experimental method are the same as those described in the above-mentioned embodiment and will not be described again here.
[0103] The corneal contact lens material formed by the hot pressing step is further processed into a corneal contact lens, and the corneal contact lens is subjected to a compression breaking strength test.
[0104] Through experiments, we obtained Figure 8 The experimental results in Figure 8 It can be seen that when the specified temperature T in the hot pressing step is 20°C and 40°C higher than the glass transition temperature Tg of the blank 4, a higher strength corneal contact lens can be obtained. That is to say, when the conditions of T-Tg>0 and T-Tg<30°C are met, the load value at the time of compression failure is the highest and the change is the smallest.
[0105] [Experimental Example 2]
[0106] The glass transition temperature Tg of the blank 4 is 70°C.
[0107] The experimental method is the same as that in Experimental Example 1. The corneal contact lens materials are processed by hot pressing at a specified temperature T=100°C and by hot pressing at a specified temperature T=120°C, and the compression strength test is performed on the processed corneal contact lenses.
[0108] The experimental results were similar to those in Experimental Example 1. That is, when the prescribed temperature T in the hot pressing step is 30°C and 50°C higher than the glass transition temperature Tg of the blank 4, a higher strength contact lens can be obtained, that is, when the conditions of T-Tg>0 and T-Tg<50°C are met, the load value at the time of compression failure is the highest and the change is the smallest.
[0109]
Experimental Summary
[0110] By controlling the prescribed temperature T of the heat treatment device in the hot pressing step, the strength of the contact lens material can be effectively improved. When the prescribed temperature T in the hot pressing step satisfies the conditions of T-Tg>0 and T-Tg<50°C, more preferably, when the prescribed temperature T in the hot pressing step satisfies the conditions of T-Tg>0 and T-Tg<30°C, it is conducive to obtaining a contact lens material with higher strength, and on this basis, being as close to Tg as possible is a more preferred solution.
[0111] The above is an example of the processing method of the contact lens material of the present invention, and the manufacturing method of the contact lens using the contact lens material. However, it should be particularly noted that, as a preference, the hard gas permeable contact lens for orthokeratology is more suitable for manufacturing using the processing method of the contact lens material of the present invention, and the manufacturing method of the contact lens using the contact lens material. The manufacturing steps and methods are the same as those in the above embodiment and will not be repeated.
[0112] Compared with general corneal contact lenses, hard gas permeable contact lenses are thinner and require higher mechanical properties (strength and toughness) of corneal contact lens materials. Therefore, the hard gas permeable contact lens material manufactured by the method for manufacturing corneal contact lenses using the corneal contact lens material provided by the present invention, and the hard gas permeable contact lens for corneal reshaping manufactured by the method for manufacturing corneal contact lenses of the present invention, while meeting the thickness requirements, have better performance in terms of strength and toughness.
[0113] Those skilled in the art will appreciate that, in the description of exemplary embodiments of the invention, for the purpose of streamlining the disclosure and aiding in the understanding of one or more of the various inventive aspects, the various features of the invention are sometimes grouped together in a single embodiment, figure, or description thereof. However, this method of disclosure should not be interpreted as reflecting an intention that the claimed invention requires more features than those expressly recited in each claim. On the contrary, as reflected in the appended claims, the various inventive aspects may have fewer features than all of the features of a single preceding disclosed embodiment. Therefore, the claims appended after the specific description are hereby expressly incorporated into the specific description, with each claim acting alone as a separate embodiment of the invention.
[0114] In addition, although some embodiments described herein include some features included in other embodiments but do not include other features included in other embodiments, the combination of features of different embodiments is intended to fall within the scope of the present invention and form different embodiments as will be understood by those skilled in the art. For example, in the appended claims, any of the claimed embodiments may be used in any combination.
[0115] It should be noted that the use of a particular term in describing certain features or aspects of the present invention should not be used to imply that the term is redefined herein to be limited to include any specific characteristics of the feature or aspect of the present invention associated with the term.
[0116] In the description provided herein, numerous specific details are set forth. However, it should be understood that embodiments of the present invention may be practiced without these specific details. In other instances, well-known methods, structures, and techniques are not shown in detail to avoid obscuring the understanding of this description.
Claims
1. A method for processing a corneal contact lens material, characterized in that: The steps include: A pre-processing step of providing a blank of a specified size made of a resin material; A hot pressing preparation step, placing the blank in a pressing assembly, and placing the pressing assembly and the blank as a whole in a heat treatment device with an internal temperature of a specified temperature; a hot pressing step, heating the pressing assembly and the blank as a whole for a specified time, and then pressing the blank to form a corneal contact lens material; Wherein, the relationship between the specified temperature T of the heat treatment device and the glass transition temperature Tg of the blank satisfies the conditions of T-Tg>0℃ and T-Tg<30℃; The blank comprises a copolymer of siloxane methacrylate and fluoroalkyl methacrylate.
2. The method for processing corneal contact lens material according to claim 1, characterized in that: The relationship between the predetermined temperature T of the heat treatment device and the glass transition temperature Tg of the blank satisfies the conditions of T-Tg>10°C and T-Tg<30°C.
3. The method for processing corneal contact lens material according to claim 1, characterized in that: The pressing assembly comprises a pressing seat, a pressing block and a container disposed in the pressing seat and having a space for placing the blank, wherein the blank is a columnar blank. In the hot pressing step, the pressing block is pressed downward, so that the heat-softened blank extends radially outward to fill the space of the container.
4. The method for processing a corneal contact lens material according to claim 3, wherein: The pressing assembly includes a plurality of containers stacked along the force application direction of the pressing block, and the plurality of containers are accommodated between the pressing seat and the pressing block.
5. The method for processing a corneal contact lens material according to claim 4, characterized in that: The bottom surface inside the container is formed as a convex arc surface.
6. The method for processing a corneal contact lens material according to claim 4 or 5, characterized in that: The container is an integrally formed mold.
7. The method for processing a corneal contact lens material according to claim 4 or 5, characterized in that: The container is composed of a bottomless cylindrical mold and a stripping block matched with the bottom of the bottomless cylindrical mold, and the blank is placed on the upper surface of the stripping block.
8. The method for processing a corneal contact lens material according to claim 7, wherein: The upper surface of the stripping block is formed as a convex arc surface.
9. The method for processing a corneal contact lens material according to claim 3, wherein: The specified size of the blank provided in the pretreatment step is determined according to the internal space size of the container and the hot pressing elongation of the resin material, so that the size of the blank after hot pressing matches the internal space size of the container.
10. A method for manufacturing a corneal contact lens, characterized in that: include, The cutting step is to cut the contact lens material formed by the processing method according to any one of claims 1 to 9 to manufacture the contact lens.
Citation Information
Patent Citations
Transmissive optical element manufacturing method
CN113811433A
Forming combined die for corneal contact lens base material
CN214605396U
Manufacture of gas permeating type hard contact lens
JP1999314283A